Ground State Solution for an Autonomous Nonlinear Schrödinger System - Min Liu; Jiu Liu (Journal of Function Spaces)
In this paper, we study the following autonomous nonlinear Schrödinger system (discussed in the paper), where λ,μ, and ν are positive parameters; 2∗=2N/N−2 is the critical Sobolev exponent; and f satisfies general subcritical growth conditions. With the help of the Pohožaev manifold, a ground state solution is obtained.